Designing and Implementation of Efficient (2i x j) Reversible RAM-Array Module - Alla, Srija; S H, Bharathi (International Journal of Engineering and Technology, 2018)
In the modern digital-world, power dissipation in microprocessors is becoming a significant challenge for the researchers to design an efficient reversible logic circuit. Thus, study on reversible logic design has been rapidly increased in present days for its application in Nano technology as well as in low energized VLSI design etc. In this current study, have realized a QC (i.e. quantum-cost) efficient (2i x j) reversible RAM array module with (3 x 3) New Modified Fredkin (NMF) reversible gate. Additionally, have introduced a Reversible D-Flip-Flop (RDFF) with less QC, and Reversible (i x 2i) decoder which produces the effective results in terms of QC and garbage-outputs. Finally, the study analyzed the designed architecture in terms of worst case delay.Â Â